2020
DOI: 10.4236/ojas.2020.101007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Phytogenic Extract Herbs on Physiological Status and Carcass Traits of Broiler Chickens

Abstract: This paper was conducted to monitor the effect of mixed essential oils (AROMIX  ) as phytogenic extract herbs administration in drinking water on growth performance, hematological, biochemical, immunological statuses and carcass traits of broiler chickens. A total number of 240 unsexed broiler chicks (Cobb-500) strain, were randomly divided to four equal groups, 60 chicks each at seven days of age. The first group drank tap water (control), the second, third and fourth group were drank the same water, adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(24 reference statements)
1
5
1
Order By: Relevance
“…Likewise, the birds when supplementing an unbalanced diet, these cellular disturbances can cause this enzyme to escape from cells into blood plasma (41). The results got in the current study are disagree with Abd El-Hady et al (31) who reviewed the influences of nourished diet encompasses with oregano to the broiler chicks had significant differ from control groups of total protein with a diminution of cholesterol in treated group with oregano relative to control groups. The reason suggested that the influence of oregano on metabolism of protein may be associated to enhancement of intestinal amino acids absorption in acidic environments that subsequently improves protein creation, or the elevation level of albumin has been sign of the protein retention in the body.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Likewise, the birds when supplementing an unbalanced diet, these cellular disturbances can cause this enzyme to escape from cells into blood plasma (41). The results got in the current study are disagree with Abd El-Hady et al (31) who reviewed the influences of nourished diet encompasses with oregano to the broiler chicks had significant differ from control groups of total protein with a diminution of cholesterol in treated group with oregano relative to control groups. The reason suggested that the influence of oregano on metabolism of protein may be associated to enhancement of intestinal amino acids absorption in acidic environments that subsequently improves protein creation, or the elevation level of albumin has been sign of the protein retention in the body.…”
Section: Discussioncontrasting
confidence: 95%
“…Similarly, Silva-Vázquez et al (30) that conclude revelation the positive effect of two type of oregano oils at 0.40 g/kg in the diet on broiler blood Figure specially leukocytes and lymphocytes percentage without changing hemoglobin and hematocrit and oregnum acts as a replacement to artificial antioxidants. Another researcher improved significantly the value of hemoglobin and percentage of lymphocytes on broiler that treated with oregano, because thyme have high concentration of iron to stimulate hemoglobin production, also occurrence flavonoids which have antioxidant properties that able to improve of blood figure (31). The proportion of lymphocytes in this experiment did not differ in G1, G2 and G4 in line with the results of Savoini et al (32), who reported that lymphocytes were increased in piglets when fed by 300 mg/kg of oregano extracts, the increase of some WBC differential values are an indicator for the non-specific stimulation of cellular immunity and demonstrates that the influence of immune response can be determined in any case by the recorded parameters of the blood picture.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this finding is consistent with the results of [32], who suggested that 0.25 and 0.5 g/kg of probiotics (Bacillus subtilis) did not result in any significant changes in the tibiotarsal index and medullary diameter, compared to all treatment groups and the control group, but that they contrasted in diaphysis diameter and robusticity index, where no significant differences were found in comparison to the control. The results of the current research are similar to those reported by [41]; no significant differences in tibia-breaking strength were observed in broilers fed 50 mg/kg of thyme essential oil, rosemary, or French lavender alone or in combinations at a level of 25 mg/kg. While these data contradict the findings of [42], who showed a significant increase in the tibia weight and tibia length of broilers in the diet containing the phytogenic compound (thyme cm/liter of water) compared to treatment groups with (1cm/ litter of water and 1cm /15 litter) and to controls.…”
Section: Tibia Bone Qualitysupporting
confidence: 90%
“…In the present study, compared to the control group, birds given S. platensis extract had a significantly enhanced lipid profile ( Table 7 ). Similarly, Abd El-Hady and El-Ghalid (2018) found that broiler meals supplemented with 3 to 6% Spirulina considerably reduced total cholesterol, triglycerides, and low-density lipoprotein levels when compared to the control group. The reduction in the serum lipid profile of broiler chickens fed dietary Spirulina may be due to Spirulina supplementation, which increases the Lactobacillus population ( Mariey et al, 2012 ).…”
Section: Discussionmentioning
confidence: 82%